2014
DOI: 10.1186/1477-7525-12-47
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of long-term quality of life after cavotricuspid isthmus ablation for typical atrial flutter

Abstract: BackgroundCavotricuspid isthmus (CTI) ablation is the treatment of choice in preventing recurrences of typical atrial flutter (AFl). However, little is known about long-term quality of life (QoL) after CTI ablation.Methods and resultsFrom 01/2003 to 05/2005, 94 patients who consecutively underwent typical AFl ablation were included in the study. An SF-36 health questionnaire was self-administered before ablation and at follow-up. Transformed scores were calculated, adjusted for age and sex and then normalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“… 12 , 13 Ablation of AFL in unselected patients is associated with decreased hospitalizations, emergency department visits, development of subsequent AF, 18 and improved quality of life. 1 , 19 Guidelines therefore recommend it as first‐line therapy. 20 However, few studies included patients with HF, and there are no randomized controlled trials in patients with AFL and HF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 Ablation of AFL in unselected patients is associated with decreased hospitalizations, emergency department visits, development of subsequent AF, 18 and improved quality of life. 1 , 19 Guidelines therefore recommend it as first‐line therapy. 20 However, few studies included patients with HF, and there are no randomized controlled trials in patients with AFL and HF.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, single‐procedure ablation success rates exceed 90% for typical and atypical AFL, 2 with associated acute complication rates of 3–11% 12,13 . Ablation of AFL in unselected patients is associated with decreased hospitalizations, emergency department visits, development of subsequent AF, 18 and improved quality of life 1,19 . Guidelines therefore recommend it as first‐line therapy 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Cavotricuspid isthmus (CTI) ablation is the treatment of choice for recurrent and symptomatic AFL, with a high procedural success rate [24] and significant QoL improvement [25]. However, coexistent AF is frequently unmasked after CTI ablation for AFL [14,26].…”
Section: Differences Between Patients With and Without Cavotricuspid ...mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that stand-alone pulmonary vein isolation prevents recurrence of AFL, even without CTI ablation [29]. Considering the strong impact of CTI ablation on the arrhythmia recurrence and that symptoms are usually linked to the arrhythmia burden [30], as well as the fact that an improvement in quality of life could be demonstrated for patients after CTI ablation [25], we subdivided the group of patients with coexistent AF and AFL in those with and without a history of CTI ablation. We observed that patients who underwent CTI ablation had significantly more symptoms, and particularly more palpitations, than patients without CTI ablation and patients with AF only.…”
Section: Differences Between Patients With and Without Cavotricuspid ...mentioning
confidence: 99%
“…Descrevem-se, quanto à avaliação psicométrica, na figura 4, os testes realizados em cada questionário, sendo que apenas um estudo não apresentava avaliação psicométrica 20 e, quanto à avaliação da confiabilidade, dez questionários avaliavam a consistência interna por meio do α- Lembra-se que esta revisão integrativa buscou identificar, na literatura, instrumentos disponíveis que avaliam sintomas e/ou QVRS em pacientes com taquiarritmias. Encontraram-se estudos que avaliam a QVRS em pacientes com arritmia, submetidos a procedimentos de ablação, [34][35][36][37][38][39][40][41][42][43][44][45][46] ao tratamento farmacológico das arritmias, [47][48][49][50][51][52][53] bem como em pacientes com FA submetidos à intervenção educacional de Enfermagem, além de estudos que abordam a QVRS, em geral, de DISCUSSÃO pacientes, incluindo aspectos psicológicos como a ansiedade e depressão, [57][58][59][60][61][62][63][64] bem como atividades da vida diária, como sono e direção de veículos. Encontraram-se, quanto aos instrumentos, estudos referentes a 11 questionários.…”
unclassified